Impacts de la réalisation d'un atlas électronique en région : le cas du Saguenay-Lac-Saint-Jean au Québec - Majella-J. Gauthier (Unité Mixte de Recherche 8504 Géographie-cités, 2003)
Since the start of the project of the electronic Atlas of Québec and its regions, the implementation of regional atlases began timidly but seriously. The works produced in the regions of Bas-Saint-Laurent and Saguenay-Lac-Saint-Jean are initiatives that not only have inclined researchers to use new ways to communicate information but also have contributed to elaborate useful geographic "savoirs". The Project of the electronic atlas of the Saguenay-Lac-Saint-Jean, which has been running for some years, may give evidence of the important role played by a team of researchers in a region where social-economic problems, questions of development and land planning, utilization of natural resources, and municipal re-structuration are top priority.